Respuesta :

39285

Answer:

1. 4(2h+g)

2. 4h+4h+3g+g

3. 2(4h+2g)

Step-by-step explanation:

1. 4 times 2h= 8h, 4 times g=4g

2. 4h+4h=8h, 3g+g=4g

3. 2 times 4h=8h, 2 times 2g=4g

can you mark me brainliest please

Answer:  B,  C , and E are the answers

Step-by-step explanation:

First solve the expressions by breaking it down.  

2h + g   Nothing can be done to this expression because it is already broken down.

4(2h + g)  Apply the distributive property to break it down.  

 4(2h) + 4(g)

=    8h + 4g  

4h + 4h  + 3g + g   Combine like terms to break this one down

(4h + 4h) + (3g + g)

= 8h + 4g  

1/4(2h + g)    Apply the distributive property to break it down.  

=  1/2h + 1/4g  

2(4h + 2g)     Apply the distributive property to break it down.    

= 8h  + 4g    

1/8(8h + 4g)   Apply the distributive property to break it down.  

  1h + 1/2g  

 

ACCESS MORE